2017
DOI: 10.1037/xlm0000282
|View full text |Cite
|
Sign up to set email alerts
|

Slower reacquisition after partial extinction in human contingency learning.

Abstract: Extinction is a very relevant learning phenomenon from a theoretical and applied point of view. One of its most relevant features is that relapse phenomena often take place once the extinction training has been completed. Accordingly, as extinction-based therapies constitute the most widespread empirically validated treatment of anxiety disorders, one of their most important limitation is this potential relapse. We provide the first demonstration of relapse reduction in human contingency learning using mild av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…In CET, one way to implement this technique is by encouraging individuals to occasionally consume small amounts of food during cue exposure exercises, in order to learn that eating a small amount of food is no longer a cue for overeating [ 13 ]. In support, animal and human appetitive conditioning [ 51 , 76 ], as well as fear conditioning studies [ 77 , 78 ], has reported evidence for occasional reinforcements during extinction to reduce relapse of responding (i.e., rapid reacquisition). In studies on CET, occasional reinforced extinction has not yet been studied in isolation, but some studies have incorporated this technique in exposure sessions by letting participants take small bites of high-calorie food previously associated with overeating [ 74 •, 75 ].…”
Section: Cue Exposure Therapy: Effects Working Mechanisms and Its Omentioning
confidence: 99%
“…In CET, one way to implement this technique is by encouraging individuals to occasionally consume small amounts of food during cue exposure exercises, in order to learn that eating a small amount of food is no longer a cue for overeating [ 13 ]. In support, animal and human appetitive conditioning [ 51 , 76 ], as well as fear conditioning studies [ 77 , 78 ], has reported evidence for occasional reinforcements during extinction to reduce relapse of responding (i.e., rapid reacquisition). In studies on CET, occasional reinforced extinction has not yet been studied in isolation, but some studies have incorporated this technique in exposure sessions by letting participants take small bites of high-calorie food previously associated with overeating [ 74 •, 75 ].…”
Section: Cue Exposure Therapy: Effects Working Mechanisms and Its Omentioning
confidence: 99%
“…Although only two cues were used here, A and B, the counterbalancing procedure included three different geometrical figures as cues. As in other experiments from our laboratory (see, for example, Morís et al, 2017) that included three cues, we decided not to alter the counterbalancing routine used here as if anything using three cues would make it more likely that any observed effects were independent of the specific geometrical figures used as cues A and B. All visual stimuli were presented against a light grey coloured background (RGB values of 128, 128, and 128) in the centre of the screen.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, we followed Morís et al’s (2017) Experiment 3 protocol, which used a gradual ORE treatment, as described previously. The procedure included three phases.…”
Section: Overview Of the Experimentsmentioning
confidence: 99%
See 2 more Smart Citations